Exploring the Prospects and Challenges of Sustainable Waterfront Development in Bangladesh - Reza, Farhadur; Abedin, A.B.M. Siddiqul; Amin, Yeasir Mohammad; Lopa, Lutfun Nahar (Exploration अन्वेषण, 2026)
Urban waterfronts are dynamic social and ecological systems that embody the relationship between people and water. This study investigates the prospects and challenges of developing a sustainable urban waterfront along the Turag River in Dhaka, Bangladesh. The study employed an observational structured checklist and short interviews for qualitative data collection of the Turag riverfront area. The data encompasses daily activities and available facilities to draw a current scenario of the waterfront, sorted and organised under the theme of the sustainability pillars. The collected data was analysed thematically to draw an interpretation to fulfil the study objectives. Results reveal that while the waterfront supports multiple livelihoods, leisure, and transportation activities, it suffers from pollution, unequal accessibility, and inadequate management. Findings emphasise the need for participatory governance, ecological restoration, and inclusive design aligned with national policies such as the Bangladesh Delta Plan 2100. Based on the findings, the study tries to advocate for some recommendations for the sustainable future of the Turag River.